Ankle antagonist coactivation in the double-support phase of walking: Stroke vs. healthy subjects. (3rd July 2015) - Silva, Augusta; Sousa, Andreia S. P.; Silva, Cláudia; Tavares, João Manuel R. S.; Santos, Rubim; Sousa, Filipa
Abstract: Introduction : Lesions in ipsilateral systems related to postural control in the ipsilesional side may justify the lower performance of stroke subjects during walking. Purpose . To analyze bilateral ankle antagonist coactivation during double support in stroke subjects. Methods : Sixteen (8 females; 8 males) subjects with a first isquemic stroke and 22 controls (12 females; 10 males) participated in this study. The double-support phase was assessed through ground reaction forces and the electromyography of ankle muscles was assessed in both limbs. Results : The ipsilesional limb presented statistically significant differences from the control when assuming specific roles during double support. The tibialis anterior and soleus pair was the one in which this atypical behavior was more pronounced. Conclusion : The ipsilesional limb presents a dysfunctional behavior when a higher postural control activity was demanded.